2020
DOI: 10.1371/journal.pone.0241226
|View full text |Cite
|
Sign up to set email alerts
|

Full-dose hepatitis B virus vaccination coverage and associated factors among health care workers in Ethiopia: A systematic review and meta-analysis

Abstract: Introduction The hepatitis B vaccine is the backbone of hepatitis B prevention. All health care workers must receive a full-dose (3-dose vaccine series) to achieve >90% protection against hepatitis B virus. There is limited evidence available on vaccination coverage of HBV among health care workers in Ethiopia. Therefore, the objective of this study was to estimate the national full-dose hepatitis B vaccination coverage and the associated factors among health care workers in Ethiopia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 34 publications
8
18
0
Order By: Relevance
“…The variation in the vaccination rates might be due to differences in socioeconomic status, sample sizes, standards of health care services across the countries, and availability of the vaccine. However, our finding was consistent with previous similar studies reported from different countries [ 7 , 14 , 21 , 24 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The variation in the vaccination rates might be due to differences in socioeconomic status, sample sizes, standards of health care services across the countries, and availability of the vaccine. However, our finding was consistent with previous similar studies reported from different countries [ 7 , 14 , 21 , 24 ].…”
Section: Discussionsupporting
confidence: 94%
“…The WHO’s targeted to eliminate HBV in 2030 [ 20 ]. However, knowledge, attitude, awareness, access to screening, and vaccination of health care providers remain poor in many developing countries including Ethiopia [ 14 ]. Vaccination of health science students before starting their hospital attachments is crucial to control the disease burden, protect them from infection, and reduce the risk of nosocomial infection.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the hepatitis B vaccination coverage rates showed an increasing trend that was statistically significant with regard to education level, a finding that is in accordance with the results previously reported by both Zhu et al [20] and Awoke et al [22]. This may be why an increased awareness of HBV and hepatitis B vaccination and a higher acceptance of vaccination are observed among the highly educated general population [23].…”
Section: Discussionsupporting
confidence: 93%
“… 1 , 14 , 18 In addition, our finding was lower than the national prevalence of full-dose hepatitis B vaccination coverage among healthcare workers in Ethiopia which was 20.04% (95% CI 13.83, 26.26). 19 It was also lower than findings from a similar systematic review and meta-analysis conducted in America and China, where the prevalence of vaccination coverage was 63.4% and 60.0%, respectively. 20 , 21 Hepatitis B vaccination is the pillar of HBV prevention.…”
Section: Discussionmentioning
confidence: 63%